Dietary habits and energy balance in an under 21 male international soccer team - Caruana Bonnici, D.; Akubat, I.; Greig, M.; Sparks, A.; Mc Naughton, L. R. (Research in Sports Medicine, 2018)
Soccer presents a metabolic challenge which is not necessarily matched by players` habitual dietary intake. To examine the effects of a bespoke diet, 22 players completed the Ball Sport Endurance and Sprint Test (BEAST90mod) protocol, followed by 4 days of regulated nutritional intake. The diet consisted of 10 g·kg-1 body mass (BM) and 1.7 g·kg-1 BM of carbohydrate and protein, respectively. On day 5, players followed a prematch nutritional strategy of 7 g·kg-1 BM of carbohydrate and 1 g·kg-1 BM of protein divided into three meals and then repeated the BEAST90mod. The players` pre-intervention intake consisted of 49 ± 7.1% or 3.5 g ± 1.0 g·kg-1 BM for carbohydrate and 19 ± 3.8% of total daily energy intake or 1.3 g ± 0.5 g·kg-1 BM for protein. Following the tailor-made dietary intervention, players ran an additional 887 ± 233 m (8.1%; d = 2.4). An acute dietary intervention provided a positive effect on a valid simulated soccer match play test.